Rugose Morphotype in Salmonella Typhimurium and Salmonella Heidelberg Induced by Sequential Exposure to Subinhibitory Sodium Hypochlorite Aids in Biofilm Tolerance to Lethal Sodium Hypochlorite on Polystyrene and Stainless Steel Surfaces - Bansal, Mohit; Nannapaneni, Ramakrishna; Kode, Divya; Chang, Sam; Sharma, Chander S.; McDaniel, Christopher; Kiess, Aaron (Frontiers in Microbiology, 2019)
Salmonella biofilms act as a continuous source for cross-contamination in the food processing environments. In this study, a stable rugose morphotype of Salmonella was first induced by sequential exposure to subinhibitory concentrations (SICs) of sodium hypochlorite (NaOCl) (ranging from 50 to 300 ppm over 18-day period) in tryptic soy broth. Then, rugose and smooth morphotypes of S. Typhimurium ATCC 14028 and S. Heidelberg ATCC 8326 were characterized for biofilm forming abilities on polystyrene and stainless steel surfaces. Rugose morphotype of both ATCC 14028 and ATCC 8326 exhibited higher EPS formation than smooth morphotype (P < 0.05). Also, the SICs of NaOCl (200 or 300 ppm in broth model) increased the biofilm formation ability of rugose morphotype of ATCC 8326 (P < 0.05) but decreased that of ATCC 14028. The 2-day-old Salmonella biofilms were treated with biocidal concentrations of 50, 100 or 200 ppm NaOCl (pH 6.15) in water for 5, 10 or 20 min at room temperature. The biofilm reduction in CFU/cm2 for the rugose was lower than the smooth morphotype on both surfaces (P < 0.05) by lethal NaOCl in water. Scanning electron micrographs on both polystyrene and stainless steel surfaces demonstrated that the rugose morphotype produced a denser biofilm than the smooth morphotype. Transmission electron micrographs revealed the cell wall roughness in rugose morphotype that which may help in tolerance to NaOCl. The gene expression data indicate that the expression of biofilm regulator (csgD), curli (csgA, csgB, and csgC) and cellulose (bcsE) was significantly increased in rugose morphotype when induced by sequential exposure of NaOCl SICs. These findings reveal that the rugose morphotype of S. Typhimurium and S. Heidelberg produced significantly denser biofilm on food-contact surfaces which also increased with sequential exposure to SICs of NaOCl in the case of S. Heidelberg and these biofilms were more tolerant to biocidal NaOCl concentrations commonly used in the food processing plants.